The Use of Natural Health Products Especially Papaya Leaf Extract and Dandelion Root Extract in Previously Untreated Chronic Myelomonocytic Leukemia. (18th December 2018) - Rahmat, Leena T.; Damon, Lloyd E.
Abstract : Chronic myelomonocytic leukemia (CMML) is a clonal hematopoietic disorder which shares clinical and morphological features of myelodysplastic syndrome and myeloproliferative neoplasms. Conventional therapeutic options include hydroxyurea, hypomethylating agents, and systemic chemotherapy, which are all palliative measures and are associated with potential side effects. Allogeneic hematopoietic cell transplantation is the only curative option. Natural health products such as papaya leaf extract and dandelion root extract have been shown to demonstrate anticancer activity in preclinical and clinical studies, respectively. We present a case study of a 76-year-old male with previously untreated CMML, whose hematological parameters remained stable and whose bone marrow blast counts vastly improved while taking papaya leaf extract and dandelion root extract.